The earth is weeping : the epic story of the Indian wars for the American West - Cozzens, Peter, 1957- (New York : Alfred A. Knopf, 2016)
"With the end of the Civil War, the nation recommenced its expansion onto traditional Indian tribal lands, setting off a wide-ranging conflict that would last more than three decades. In an exploration of the wars and negotiations that destroyed tribal ways of life even as they made possible the emergence of the modern United States, Peter Cozzens gives us both sides in comprehensive and singularly intimate detail. He illuminates the encroachment experienced by the tribes and the tribal conflicts over whether to fight or make peace, and explores the squalid lives of soldiers posted to the frontier and the ethical quandaries faced by generals who often sympathized with their native enemies"--Amazon.com.
Prologue: Our Children Sometimes Behave Badly -- The Plains Aflame -- Red Cloud's War -- Warrior and Soldier -- Hancock's War -- The Last Treaty -- Of Garryowen in Glory -- The Bloody Policy of Peace -- Tragedy in the Lava Beds -- The Buffalo War -- No Rest, No Peace -- Sitting Bull and Crazy Horse -- The Thieves' Road -- Guard Us Against All Misfortune -- Last Stand -- The Great Father's Fury -- A Warrior I Have Been -- I Will Fight No More Forever -- The Utes Must Go! -- Return to Apacheria -- Like So Many Vultures, Greedy for Blood -- Once I Moved Like the Wind -- A Clash of Visions -- The Place of the Big Killings.
"This is a Borzoi Book"--Title page verso.
Includes bibliographical references (pages 471-524) and index.
Keywords: Indians of North America -- Wars -- 1866-1895.; Indians of North America -- Wars -- 1866-1895.; HISTORY -- Native American; HISTORY -- United States -- 19th Century; HISTORY -- Military -- United States; Indians of North America -- Wars -- 1866-1895.